CRISPR/Cas9 in Cancer Immunotherapy: Animal Models and Human Clinical Trials - Khalaf, Khalil; Janowicz, Krzysztof; Dyszkiewicz-Konwińska, Marta; Hutchings, Greg; Dompe, Claudia; Moncrieff, Lisa; Jankowski, Maurycy; Machnik, Marta; Oleksiewicz, Urszula; Kocherova, Ievgeniia; Petitte, Jim; Mozdziak, Paul; et al. (Genes, 2020)
Even though chemotherapy and immunotherapy emerged to limit continual and unregulated proliferation of cancer cells, currently available therapeutic agents are associated with high toxicity levels and low success rates. Additionally, ongoing multi-targeted therapies are limited only for few carcinogenesis pathways, due to continually emerging and evolving mutations of proto-oncogenes and tumor-suppressive genes. CRISPR/Cas9, as a specific gene-editing tool, is used to correct causative mutations with minimal toxicity, but is also employed as an adjuvant to immunotherapy to achieve a more robust immunological response. Some of the most critical limitations of the CRISPR/Cas9 technology include off-target mutations, resulting in nonspecific restrictions of DNA upstream of the Protospacer Adjacent Motifs (PAM), ethical agreements, and the lack of a scientific consensus aiming at risk evaluation. Currently, CRISPR/Cas9 is tested on animal models to enhance genome editing specificity and induce a stronger anti-tumor response. Moreover, ongoing clinical trials use the CRISPR/Cas9 system in immune cells to modify genomes in a target-specific manner. Recently, error-free in vitro systems have been engineered to overcome limitations of this gene-editing system. The aim of the article is to present the knowledge concerning the use of CRISPR Cas9 technique in targeting treatment-resistant cancers. Additionally, the use of CRISPR/Cas9 is aided as an emerging supplementation of immunotherapy, currently used in experimental oncology. Demonstrating further, applications and advances of the CRISPR/Cas9 technique are presented in animal models and human clinical trials. Concluding, an overview of the limitations of the gene-editing tool is proffered.
Keywords: animal models; modely nemocí na zvířatech; klinické zkoušky jako téma; preklinické hodnocení léčiv; Neoplasms; Immunotherapy, Adoptive; cancer; editace genu; genetická terapie; Disease; individualizovaná medicína; experimental oncology; Genetic Therapy; Gene Editing; Immunotherapy; CRISPR-Cas Systems; Animals; lidé; Humans; Drug Evaluation, Preclinical; zvířata; imunoterapie adoptivní; Disease Models, Animal; imunoterapie; CRISPR-Cas systémy; nemoc; nádory; Precision Medicine; genome editing; Clinical Trials as Topic